The Many vs. the Few (The Hastings Center report, 2012)
“The Many vs. the Few”: letters from Doris T. Zallen, Paul T. Menzel, Christopher McCabe, Robert J. Wells, and George Loewenstein about “Which Orphans Will Find a Home? The Rule of Rescue in Resource Allocation for Rare Diseases” and “Reasonable Disagreement about Identified vs. Statistical Victims” (Jan-Feb 2012), with replies from Emily Largent and Norman Daniels